Numerical Study of the Flow Fields in Downburst with Consideration of the Rough Condition on the Ground - Xiaoyu Luo; Chong Zhang; Shishu Xiong; Zhenqing Liu (Salehan Institute of Higher Education, 2018)
The downburst is an extreme weather condition whose resulting load will affect the stability of the building structures. The characteristic of downbursts is required during the design of buildings. In order to achieve the characteristics of the downbursts, large eddy simulation (LES) is adopted. The method impinging jet is used to reproduce the downbursts, meanwhile smooth and rough ground conditions are examined. The setting of the rough layer of the ground is done by using the immersion boundary method (IBM). After the simulation, the wind field is decomposed into the mean component and the turbulence component. In this paper, the radial wind speed profile and the wind speed time diagram of the simulation experiment are compared with the previous measured data and the simulation results. This paper reveals that the radial wind speed is the key part of the downburst wind speed, and it rapidly increases with height. It is also found that the rough ground will cause the peak radial velocity to move up, which is consistent with the change of the main annular vorticity in vortex cloud image analysis. Finally, the turbulence intensity is found to be relatively small at the position where the radial wind speed is relatively large.